PENGENALAN PERMAINAN TRADISIONAL KEPADA ANAK DALAM RANGKA MELESTARIKAN BUDAYA LOKAL: Introducing Children to Traditional Games in Order to Preserve Local Culture - Aminullah Aminullah; Novita Listyaningrum; Ida Ayu Ketut Marini; Ni Luh Ariningsih Sari; Ni Made Nia Bunga Surya Dewi; Gede Tusan Ardika; Aline Febriany Loilewen; I Gusti Made Subrata; Liya Apriana (Yayasan Al-Amin Qalbu, 2026)
The rapid development of digital technology has shifted children's interests from traditional games to gadgets. This situation threatens the preservation of local cultural heritage, which is rich in noble values. This community service aims to introduce and practice traditional games to children as an effort to preserve local culture. The method of implementing the community service is carried out through active participation with a descriptive approach. The results of the community service show that introducing traditional games to children, followed by traditional game competitions, can increase children's joy. Children are still enthusiastic about participating in traditional games if supported by the environment, starting from support from parents, community leaders and youth, and the village government. Although today's children are contaminated with gadgets, children's enthusiasm and enthusiasm for traditional games remain high, depending on the environment. When these games are held regularly, they can preserve local culture.